Peningkatkan Kemampuan Motorik Kasar Anak Melalui Permainan Trompa Batok Kelapa di Paud Gentaralia Desa Talang Kemang Kabupaten Seluma - Helen Soptyana; Ela Pebriani; Mimpira Haryono (Jurnal Multidisiplin Dehasen (MUDE), 2022)
The purpose of this study was to determine whether the coconut shell trompa game could improve gross motor skills in children at Gentaralia preschool in Talang Alai village, Seluma district. Class Action Research (CAR) which is focused on classroom situations, or commonly known as classroom action research, the procedures used are in the form of cycles. The main subjects in this study were the children of group B, totaling 20 children. This Classroom Action Research uses the John Elliot model where each cycle consists of four main activities, namely planning, implementation, observation, and reflection which are carried out through two cycles, namely cycle I and cycle II, each cycle consisting of one meeting. Data collection techniques using the method of observation and documentation. Data analysis was carried out descriptively qualitative-quantitatively with the emphasis used to determine the improvement of the process expressed in a predicate, while quantitative data analysis was used to determine the increase in results using percentages. The results of increasing the emotional social ability of children in the Gentaralia PAUD Unit in the first cycle of the first meeting was 66.5% and in the second cycle of the second meeting an increase of 98% was found. The conclusion of this research is that coconut shell trompa media can improve gross motor skills of children in group B in Talang Kemang Village, Semidang Alas Maras District, Seluma Regency, it is proven that in cycle II there is a significant increase, the percentage of achievement is 98% with very good developing criteria (BSB).